Plankton Community Structure in Kasiak Island Waters Pariaman City, West Sumatra Province - Febbyolla, Selfi Anidal; Siregar, Sofyan Husein; Nurrachmi, Irvina (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This study was conducted in September 2022 in Kasiak Island Water, Pariaman City, West Sumatra Province. This study aimed to analyze the community structure of phytoplankton and zooplankton and the relationship between the abundance of phytoplankton and zooplankton in the waters of Kasiak Island. The method used is the survey method. Plankton sampling was carried out at four stations with three sampling points. Plankton samples were obtained by filtering 100 L of surface water to 125 mL and then analyzed in the laboratory. The results obtained were 21 species of phytoplankton and 11 species of zooplankton. The average abundance of phytoplankton in the morning ranged from 923.15–2400.19 ind/L, and during the day ranged from 1200.09–2,492.50 ind/L. The average abundance of zooplankton in the waters of Kasiak Island in the morning went from 369,26–1,200.09 ind/L and, during the day, ranged from 369,26–1,384.72 ind/L. Phytoplankton biological indicators such as the diversity index (H') in the morning ranged from 0.6096–2.3075 and during the day ranged from1.3894–2.0129, the uniformity index (E) in the morning ranged from 0.4844–0.9851 and during the day ranged from 0.9060–0.9624, and the dominance index (D) in the morning ranged from 0.2181–0.6617 and during the day ranged from 0.2833–0.4248. While zooplankton biological indicators such as the diversity index (H') in the morning ranged from 0.2704–0.8617 and during the day ranged from 0.3333–1.1950, the uniformity index (E) in the morning ranged from 0.2704–0.6667 and during the day ranged from 0.3333–0.6667, and the dominance index (D) in the morning ranged from0.6111–0.8750 and during the day ranged from 0.5278–0.8333. The relationship between the abundance of phytoplankton and zooplankton in the morning and during the day is a moderate (positive). The regression equation in the morning isY = 0.1356x + 434.5 3and during the day it isY = 0.1845x + 362.01.